Marketing strategy and the hunt for era V. Issue 9 (12th June 2020) - Godfrey, Richard; Higgins, Matthew
ABSTRACT: This paper is a response to a recent special issue of the Journal of Marketing Management in which Shelby Hunt celebrates the achievements of 40 years of marketing strategy. In noting the passing of the 'old guard', Hunt calls on a new generation of scholars to meet the challenges confronting marketing and to develop new theories and frameworks to advance Marketing Strategy into Era V. We take for our inspiration Hunt's own words, specifically his reference to the 'promising' and 'problematic' that he uses to characterise the current and latent state of marketing strategy. To build our vision and map out our agenda we offer an alternative reading of this discipline through the idea of Marketing Strategy as Discourse (MSAD). Within the paper, we outline the role that discourse can perform as a resource to reconfigure our appreciation of marketing strategy.